Palliative long-term abdominal drains versus repeated drainage in individuals with untreatable ascites due to advanced cirrhosis: study protocol for a feasibility randomised controlled trial - Lucia Macken (Trials, 2018)
Abstract Background UK deaths due to chronic liver diseases such as cirrhosis have quadrupled over the last 40 years, making this condition now the third most common cause of premature death. Most patients with advanced cirrhosis (end-stage liver disease [ESLD]) develop ascites. This is often managed with diuretics, but if refractory, then the fluid is drained from the peritoneal cavity every 10–14 days by large volume paracentesis (LVP), a procedure requiring hospital admissions. As the life expectancy of patients with ESLD and refractory ascites (if ineligible for liver transplantation) is on average ≤ 6 months, frequent hospital visits are inappropriate from a palliative perspective. One alternative is long-term abdominal drains (LTADs), used successfully in patients whose ascites is due to malignancy. Although inserted in hospital, these drains allow ascites management outside of a hospital setting. LTADs have not been formally evaluated in patients with refractory ascites due to ESLD. Methods/design Due to uncertainty about appropriate outcome measures and whether patients with ESLD would wish or be able to participate in a study, a feasibility randomised controlled trial (RCT) was designed. Patients were consulted on trial design. We plan to recruit 48 patients with refractory ascites and randomise them (1:1) to either (1) LTAD or (2) current standard of care (LVP) for 12 weeks. Outcomes of interest include acceptability of the LTAD to patients, carers and healthcare professionals as well as recruitment and retention rates. The Integrated Palliative care Outcome Scale, the Short Form Liver Disease Quality of Life questionnaire, the EuroQol 5 dimensions instrument and carer-reported (Zarit Burden Interview) outcomes will also be assessed. Preliminary data on cost-effectiveness will be collected, and patients and healthcare professionals will be interviewed about their experience of the trial with a view to identifying barriers to recruitment. Discussion LTADs could potentially improve end-of-life care in patients with refractory ascites due to ESLD by improving symptom control, reducing hospital visits and enabling some self-management. Our trial is designed to see if such patients can be recruited, as well as to inform the design of a subsequent definitive trial. Trial registration ISRCTN, ISRCTN30697116. Registered on 7 October 2015.